Theory and Modeling of Direct Digital Synthesizers - E. S. Klyuzhev; I. V. Ryabov; I. V. Strelnikov; P. M. Yuriev (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The article considers the problems of the design of direct digital synthesizers, based on the method of the direct digital frequency and signal synthesis, the calculation of phase changes in DDS. Block and functional electrical diagrams of a direct digital synthesizer are presented. Basic formulas for the calculation of spurious spectral components levels in DDS, while forming complex signals, are given. Structures of DDS with the switching of phase samples and DDS with quadrature outputs are presented.